Prediction of neurosensory disorders after impacted third molar extraction based on cone beam CT Maglione's classification: A pilot study - Sally Awad; Sara M. ElKhateeb (Elsevier, 2021)
Background: Surgical difficulty assessment in the extraction of impacted mandibular third molars is a constant challenge for oral surgeons. Aim: The first aim was to apply Maglione's new classification on patients that needed surgical extraction of impacted mandibular third molars, and the second aim was to study the correlation of the classification classes with the occurrence of postoperative neurosensory disorders. Materials & methods: The present prospective clinical trial pilot study was conducted on patients attending oral and maxillofacial surgery clinics from February 2017 until January 2018 for the surgical extraction of impacted lower third molars. Results: Fifty-one out of sixty-nine patients made the surgical removal of one impacted mandibular third molar. The most common subclass was 1B (24.6%), followed by subclass 3B (23.2%). Subclass 3A and 4B showed an equal distribution of (11.6%) each, and then subclass 2B (10%). The most significant subclass was 4B with (5.9%) neurosensory disturbance. None of the patients had a permanent disturbance. Conclusion: Maglione's classification offers unique detailed description of the buccolingual relationship of MTM with IAC that could be used as a future reliable radiographic guide to reduce the risk of post-operative neurosensory disturbances after MTM surgical removal.